Translating an Evidence-Based Physical Activity Service From Context To Context: A Single Organizational Case Study - Lamontagne, Marie-Eve; Arbour-Nicitopoulos, Kelly P; Tomasone, Jennifer R; Cummings, Isabelle; Latimer-Cheung, Amy E; Routhier, François (Journal of Sports Medicine and Therapy, 2017)
Background: SCI Action Canada partnered with researchers to adapt an evidence-based leisure-time physical activity (LPTA) counselling service (Get-in-Motion (GIM). A satellite GIM service called Passez à l’action was established within a French-speaking context for persons with physical disabilities. An understanding of the determinants that infl uenced the implementation and functioning of the GIM service within the Adaptavie context are required to maximize the potential of other community-based LTPA services being successfully introduced in similar organizations. Purpose: The case study objectives are to: 1) describe the characteristics and implementation contexts of two leisure-time physical activity counselling services for Canadians with a physical disability and the adoption process that took place when the protocol was translated to a new context, and 2) elucidate, from the point of view of the service providers, the organizational determinants that could have facilitated and/or hindered the implementation and functioning of these services. Methods: Guided by the Consolidated Framework for Implementation Research, focus groups were held with the directors and staff of each service. Mixed-content and thematic analyses were then used to determine overarching themes. Results: Findings suggest that the presence of service innovators fosters ownership of the service and facilitates ongoing staff training and support. A thoughtful implementation plan should be included as a component of translation between contexts. Conclusions: Lessons learned and recommendations for future translation of similar evidence-based services to additional contexts are discussed.